2013
DOI: 10.1055/s-0033-1333914
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the Postoperative Hip

Abstract: Imaging of the postoperative hip with ultrasound can be difficult and challenging. The primary role of ultrasound is to help determine whether or not there is infection. It is difficult at times to differentiate between complex fluid and synovium. Whether fluid is infected or not cannot be determined by ultrasound criteria and aspiration, and laboratory analysis is required. Particle disease and infection cannot be reliably differentiated by ultrasound criteria. In the setting of possible infection, any fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This dilemma becomes more complex after surgery as the normal anatomic guideline and the tissue echogenicity may be changed. Further, following total hip arthroplasty, a pseudocapsule with soft tissues may look like a hypoechoic area along the femoral neck and can be confused for a joint effusion [ 5 , 6 ]. In general, a significant joint effusion and irregular distension of the pseudocapsule along with an extra-articular fluid or abscess are sufficient for diagnosing joint infections ( Fig.…”
Section: Soft Tissues Around Metal Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…This dilemma becomes more complex after surgery as the normal anatomic guideline and the tissue echogenicity may be changed. Further, following total hip arthroplasty, a pseudocapsule with soft tissues may look like a hypoechoic area along the femoral neck and can be confused for a joint effusion [ 5 , 6 ]. In general, a significant joint effusion and irregular distension of the pseudocapsule along with an extra-articular fluid or abscess are sufficient for diagnosing joint infections ( Fig.…”
Section: Soft Tissues Around Metal Hardwarementioning
confidence: 99%
“…Other indications include the evaluation of an iliopsoas tendon, a periprosthetic hematoma in patients with persistent wound drainage, an acetabular element, or bursitis ( Fig. 5 ) appearing as a septated cystic mass [ 6 ].…”
Section: Arthroplastymentioning
confidence: 99%
“…The few articles in which use of ultrasound for aspiration of hip arthroplasties is presented do not describe our technique. Craig (2013) discussed ultrasound examination of postsurgical hips, but the technique of aspiration was not presented. Eisler et al (2001) reported on a lateral approach in 80 patients with ultrasound that yielded sparse aspiration results which was insufficient to obtain cultures 23 % of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Our fluid samples, including those from hips with antibiotic spacers, obtained with lavage positively matched culture results 60 % of the A single culture due to an organism of relatively low virulence from synovial fluid or intraoperative culture was considered a contaminant. We had a low rate of aspirates: 2 % (Craig, 2013) deemed to be contaminated. Attempts to lessen the chance of contamination with skin flora in this study was performed by preparing the skin twice with 2 % chlorhexidine gluconate in 70 % isopropyl alcohol, use of sterile gloves, preparation of a sterile field large enough to allow for movement of the transducer, placement of sterile towels, and use of sterile ultrasound gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation